Medical wire and guide wire

By using medical wire made of stainless steel, the peripheral hardness is 8.0 GPa or more, and the difference between the overall hardness and the peripheral hardness is 0.7 GPa or less, the problem of insufficient resilience of the guide wire is solved, and a guide wire with excellent resilience and linearity is achieved.

CN119894546APending Publication Date: 2025-04-25ASAHI INTECC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380066799.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-05
Filing Date
2023-08-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing guidewires have shortcomings in terms of operability and resilience, and no guidewires with excellent resilience have been proposed.

Method used

A medical wire made of stainless steel is used, and the cross-sectional shape is a circle with a diameter of dmm. When the hardness is measured by the nano-indentation method, the average value of the hardness of the outer peripheral part is 8.0 GPa or more, and the difference between the average value of the overall hardness and the average value of the outer peripheral part is 0.7 GPa or less.

Benefits of technology

It realizes excellent resilience and linearity in medical wires and guidewires, and improves the operability and resilience of guidewires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894546A_ABST
    Figure CN119894546A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a medical wire rod and a guidewire having excellent restorability. A medical wire rod which is made of stainless steel, the shape of the cross-section of the wire rod is a circle having a diameter of dmm, and when the hardness of the cross-section of the wire rod is measured by a nanoindentation method, the average value of the hardness of an outer peripheral portion comprising a region surrounded by an outer peripheral edge and a circle having a distance of d / 17 mm from the outer peripheral edge is 8.0 GPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to medical wires and guidewires. Background Art

[0002] When treating stenosis in blood vessels such as the coronary arteries surrounding the heart, or treating areas of complete occlusion within a blood vessel due to calcification (e.g., chronic total occlusion: CTO, etc.), a guide wire for guiding them is inserted into the blood vessel before using treatment instruments such as balloon catheters.

[0003] For example, Patent Document 1 proposes a guide wire made of SUS304. Patent Document 2 discloses a medical treatment device wire having an average Vickers hardness of 670 or more and 770 or less at eight specific points in a cross section for the purpose of providing a medical treatment device wire having excellent fatigue resistance.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-172229

[0007] Patent Document 2: Japanese Patent No. 6596470 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, it is known that the operability of the guide wire is related to the habituation (restoration) in the above guide wire. However, a guide wire having excellent restorability has not yet been proposed.

[0010] An object of the present disclosure is to provide a medical wire and a guide wire having excellent restorability.

[0011] Methods for solving problems

[0012] In order to solve the above-mentioned problems, one embodiment of the present invention is a medical wire made of stainless steel, the cross-section of the wire is a circle with a diameter of d mm, and when the hardness of the cross-section of the wire is measured by a nanoindentation method, the average hardness of the outer peripheral portion consisting of an outer peripheral edge and an area surrounded by a circle with a distance d / 17 mm from the outer peripheral edge is 8.0 GPa or more.

[0013] The stainless steel may also be a stable austenitic stainless steel, the temperature Md of the stable austenitic stainless steel at which 50% of the work-induced martensite is generated when a 30% strain is applied, as given by Angel's formula. 30 Below -50℃.

[0014] The stabilized austenitic stainless steel may be a stainless steel according to ASTM F2581.

[0015] When the hardness of the cross section of the wire is measured by a nanoindentation method, the difference between an average value of the hardness of the entire cross section of the wire and an average value of the hardness of the peripheral portion may be 0.7 GPa or less.

[0016] The average hardness of the entire cross section of the wire may be 8.9 GPa or more.

[0017] A guide wire according to one aspect of the present disclosure includes the medical wire described above.

[0018] Effects of the Invention

[0019] The present disclosure can provide a medical wire and a guide wire having excellent restorability and linearity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A schematic cross-sectional view showing a guide wire according to an embodiment of the present disclosure.

[0021] Figure 2 This is a schematic diagram showing the results of measuring the cross section of a wire material using the nanoindentation method.

[0022] Figure 3 This is a schematic diagram of a jig used for restorability evaluation.

[0023] Figure 4 This is an explanatory diagram of the restoration evaluation.

[0024] Figure 5 This is a diagram for explaining the method of measuring the residual angle.

[0025] Figure 6 Only shows Figure 2 A diagram showing points on the outer periphery of all points in the cross section of the wire rod.

[0026] Figure 7 This is an explanatory diagram showing linear wave height. DETAILED DESCRIPTION

[0027] The inventors of the present invention have conducted intensive research on a medical wire having excellent resilience, and as a result, have found that a medical wire having excellent resilience can be obtained by setting the hardness of the outer peripheral portion of the wire cross section to a specific range. That is, the medical wire disclosed in the present invention is a medical wire made of stainless steel, the shape of the cross section of the wire is a circle with a diameter of d mm, and when the hardness of the cross section of the wire is measured by a nanoindentation method, the average hardness of the outer peripheral portion consisting of an outer peripheral edge and a region surrounded by a circle with a distance of d / 17 mm from the outer peripheral edge is 8.0 GPa or more.

[0028] The reason for improving the resilience by the above-mentioned structure has not yet been determined, but it is speculated that: when the wire is bent, the strain caused by bending is larger on the outer peripheral side than on the inner side of the wire. Therefore, even if the hardness of the inner part is high, if the hardness of the outer peripheral part is low, the outer peripheral part with a large strain is easy to deform. However, the high hardness of the outer peripheral part makes it difficult to deform, and the resilience is improved.

[0029] In the medical wire disclosed in the present invention, the shape of the cross section of the wire is a circle with a diameter of dmm. The diameter d of the circle is not limited, and can be 0.02 to 2.00 mm. When used for the guide wire described later, it is particularly preferably 0.10 to 1.00 mm, and preferably 0.20 to 0.50 mm. It should be noted that the cross section does not need to be a circle over the entire length of the wire. For example, as long as a part of the cross section is a circle, the cross section of other parts may not be a circle. In the case where a part of the cross section is a circle, the average value of the hardness of the above-mentioned peripheral portion in the part where the cross section is a circle can be within the above-mentioned range.

[0030] When the medical wire disclosed in the present invention measures the hardness of the cross section of the wire by the nanoindentation method, the average hardness of the peripheral portion consisting of the outer periphery and a circle with a distance of d / 17 mm from the outer periphery is 8.0 GPa or more. From the viewpoint of further improving the resilience and rotational operability, the average hardness of the above-mentioned peripheral portion is preferably 8.4 GPa or more, more preferably 8.9 GPa or more, and further preferably 9.0 GPa or more. The upper limit value is not limited. For example, from the viewpoint of brittleness, the average hardness of the above-mentioned cross section as a whole is preferably 12.0 GPa or less. An example of a specific calculation method for the average hardness of the above-mentioned peripheral portion is shown below.

[0031] In this specification, the hardness measurement based on the nanoindentation method is a value obtained by implementing the ISO 14577 "Instrumented Indentation Test" under the conditions of a maximum indentation load of 30mN and a dot spacing of 0.01mm or more and less than 0.02mm. For example, the dot spacing X can be determined by setting n so that "wire diameter (mm) ÷ (17×n)" is 0.01mm or more and less than 0.02mm. Specifically, in the case of measuring a wire with a diameter of 0.34mm, the dot spacing based on nanoindentation is set to 0.01mm, and the calculation is as follows: Figure 6 The hardness of the outer part is obtained by taking the average hardness of the two outer points (0.02 mm) shown in FIG. That is, the hardness of the outer part in this case can be obtained as the average of the two outer points when the nanoindentation point interval is set to "wire diameter (mm) ÷ (17 × 2)".

[0032] From the viewpoint of resilience and brittleness, the medical wire disclosed herein preferably has a difference of 0.7 GPa or less between the average value of the hardness of the entire cross section and the average value of the hardness of the outer peripheral portion consisting of the outer peripheral edge and a circle with a distance d / 17 mm from the outer peripheral edge when the hardness of the cross section of the wire is measured by nanoindentation. The difference is preferably 0.6 GPa or less, more preferably 0.5 GPa or less, and even more preferably 0.4 GPa or less.

[0033] The medical wire disclosed herein preferably has an average hardness of the entire cross section of 8.0 GPa or more. From the perspective of further improving resilience, the average hardness of the entire cross section is preferably 8.6 GPa or more, more preferably 8.9 GPa or more, and further preferably 9.4 GPa or more. The upper limit is not limited, for example, from the perspective of brittleness, the average hardness of the entire cross section is preferably 12.0 GPa or less. The average hardness of the entire cross section may be higher than the average hardness of the peripheral portion.

[0034] The residual angle of the medical wire disclosed herein is preferably 12.0° or less, more preferably 9.5° or less, and particularly preferably 7.0° or less.

[0035] For the medical wire of the present disclosure, the wave height indicating linearity is preferably 1.0 mm or less, and more preferably 0.5 mm or less. Figure 7 As shown, the wave height can be obtained by drawing a straight line from the trough of one wave of the wire rod to the trough and measuring the height of the wave peak from the straight line. When the wire rod has a plurality of waves, the wave height refers to the height of the largest wave.

[0036] The tensile strength of the medical wire material disclosed herein is preferably 2800 N / mm 2 From the perspective of further improving the recovery property, the tensile strength is more preferably 2900 N / mm 2 More than, more preferably 3000N / mm 2 Above, particularly preferably 3100 N / mm 2 The upper limit of the tensile strength of the wire is not particularly limited, but is usually 3500 N / mm 2 The tensile strength of the wire can be measured by a conventional tensile test of a metal wire (for example, a tensile test in accordance with JIS Z 2241 "Methods of Tensile Testing of Metallic Materials").

[0037] The medical wire material of the present disclosure can be manufactured by subjecting a steel material (base material) of a stable austenitic stainless steel to wire drawing, and then combining it with a specific linear process. The temperature Md at which 50% of the work-induced martensite is generated when 30% strain is applied, as given by the Angel formula, is30 The temperature is -50°C or lower. Generally, as a straightening process, there are a processing method of straightening by plastic deformation such as a rotary straightener, a wire straightener, a stretching machine, etc., and a processing method of straightening by heating such as stretching annealing. However, the present inventors have conducted intensive research and found that the above-mentioned stable austenitic stainless steel can be straightened by plastic deformation and then straightened by heating to increase the hardness of the peripheral part, thereby making it possible to produce a medical wire with excellent recovery. It was found that by going through the above process, the difference between the average hardness of the cross section and the hardness of the peripheral part can be reduced, and a wire with good linearity can be obtained.

[0038] For example, even when the above-mentioned stable austenitic stainless steel is used, the recovery is poor when linearization is performed only by plastic deformation as in Comparative Example 1 described later. It is known that by performing heat-based stretch annealing after linearization by plastic deformation, it is possible to achieve both recovery and stability as in Examples 1 to 5 described later. In addition, regarding the material, it is known that in a metastable austenitic stainless steel such as SUS304 that undergoes a work-induced martensitic transformation, excellent recovery cannot be obtained even if a stretch annealing treatment is performed after linearization by plastic deformation as in Comparative Example 2 described later.

[0039] As described above, the medical wire of the present invention is obtained for the first time by using a specific material and performing a specific process.

[0040] The medical wire material of the present disclosure is made of stainless steel, preferably a stable austenitic stainless steel, wherein the temperature Md at which 50% of the work-induced martensite is generated when 30% strain is applied is given by the following Angel equation: 30 Below -50℃.

[0041] Md 30 =551-462×(C+N)-9.2×Si-8.1×Mn-13.7×Cr-×9.5Ni-18.5×Mo…Angel

[0042] formula

[0043] Here, C, N, Si, Mn, Cr, Ni, Cu, and Mo are the amounts of each element (mass %). 30 The smaller the value of , the more stable the austenite is considered.

[0044] From the perspective of increasing the effects of solid solution strengthening and strain aging, the stainless steel is particularly preferably a high nitrogen austenitic stainless steel having a nitrogen (N) content of 0.1% by mass or more. The nitrogen content is more preferably 0.2% by mass or more, and further preferably 0.4% by mass or more. From the perspective of being able to achieve excellent fracture resistance, the nitrogen content is preferably 1.0% by mass or less, and more preferably 0.8% by mass or less.

[0045] Examples of the stainless steel include stainless steels conforming to ASTM F2581 (C: 0.15-0.25 mass%, Mn: 9.50-12.50 mass%, P: 0.020 mass% or less, S: 0.010 mass% or less, Si: 0.20-0.60 mass%, Cr: 16.5-18.0 mass%, Ni: 0.05 mass% or less, Mo: 2.70-3.70 mass%, N: 0.45-0.55 mass%, Cu: 0.25 mass% or less, Fe: balance), ASTM F138, F1314, F1586, and F2229. Stainless steels conforming to ASTM F2581 are preferred from the viewpoint of obtaining a wire having particularly excellent resilience.

[0046] The wire drawing process is not particularly limited as long as it can continuously reduce the wire diameter of the steel material. It can be a process using a die or a process using a roller. The area reduction rate of the wire material during the process is preferably 80 to 97%, for example. Here, the area reduction rate is given by (1-r1 2 / r0 2 ) × 100. r0 is the radius of the base material (wire before processing), and r1 is the radius of the drawn material (wire after processing).

[0047] As the straight line processing by plastic deformation, any method is not particularly limited as long as it can straighten the wire into a straight line, and examples thereof include roller straightening machines, wire straightening machines, stretching straightening machines, stretching machines, etc., which can be implemented alone or in combination. The straight line processing by plastic deformation can be implemented at room temperature or at a temperature that does not have a significant impact on the metal, for example, preferably at a temperature of 0°C to 100°C.

[0048] The stretch annealing treatment is performed by heating the wire while applying tension (stretching) to the wire. The tension is preferably 10 to 40% of the tensile strength, and the heating temperature is preferably 300 to 700° C. In addition, the tension is more preferably 20 to 30%, and the heating temperature is more preferably 500 to 650° C.

[0049] Hereinafter, one embodiment of the guide wire of the present disclosure will be described with reference to the drawings, but the present disclosure is not limited to only the embodiments described in the drawings.

[0050] Figure 1 This is a schematic cross-sectional view of a guide wire 1 according to an embodiment of the present disclosure.

[0051] like Figure 1 As shown, the guide wire 1 includes a core shaft 10 , a coil body 20 , a distal end joint portion 30 , and a proximal end fixing portion 40 .

[0052] The core shaft 10 is a round rod-shaped structure that gradually tapers from the base end toward the front end. The user performs a rotation operation of the guide wire 1 at the base end.

[0053] The coil body 20 is formed into a hollow cylindrical shape by spirally winding a metal wire 21 around the core shaft 10. As the material of the coil body 20, X-ray opaque materials such as gold, platinum, tungsten, tantalum, or alloys containing these elements, or stainless steel, superelastic alloys, cobalt-based alloys, etc. can also be used.

[0054] The front end joint 30 constitutes the front end of the guide wire 1 and is roughly hemispherical. As the material of the front end joint 30, silver, gold or alloys containing these metals, lead-free solder, brazing material, adhesive, etc. are used. As examples of lead-free solder and brazing material, lead-free solders such as Sn-Ag alloys, Sn-Ag-Cu alloys, Au-Sn alloys, Au-Ge alloys, silver solders, gold solders, etc. can be used.

[0055] The base end joint 40 fixes the base end of the coil body 20 to the core shaft 10. As the material of the base end joint 40, silver, gold or an alloy containing these metals, lead-free solder, brazing material or adhesive, etc. are used. As examples of lead-free solder and brazing material, lead-free solders such as Sn-Ag alloys, Sn-Ag-Cu alloys, Au-Sn alloys, Au-Ge alloys, silver solders, gold solders, etc. can be used.

[0056] The core shaft 10 is obtained by cutting the medical wire of the present disclosure and performing a taper process on the end of the wire so that the outer diameter gradually decreases toward the front end. By using the medical wire of the present disclosure, a guide wire with excellent restorability can be obtained.

[0057] Example

[0058] Next, the hardness measurement, tensile strength measurement, and recovery evaluation of the wire material of the present disclosure are described. The wire materials used for the evaluation are shown in Table 1 and Table 2. Table 1 shows the composition, wire diameter, tensile strength, and straightness of the wire drawing materials used in Examples 1 to 5 and Comparative Examples 1 to 2.

[0059] [Table 1]

[0060]

[0061] The wire drawing material 1 used in Examples 1 to 5 and Comparative Example 1 shown in Table 1 is a wire material made of stainless steel in accordance with ASTM F2581. The wire drawing material 2 used in Comparative Example 2 is a wire material made of SUS304 stainless steel.

[0062] Example 1

[0063] The wire drawing material 1 was subjected to plastic working at room temperature (25°C), and then both ends of the wire were held and stretched and annealed under heating conditions of 500 to 650°C with a tension of 60N applied to obtain a medical wire.

[0064] Example 2

[0065] A medical wire was obtained in the same manner as in Example 1 except that the heating temperature was changed to 450 to 600°C.

[0066] Example 3

[0067] A medical wire was obtained in the same manner as in Example 1 except that the heating temperature was changed to 400 to 550°C.

[0068] Example 4

[0069] A medical wire was obtained in the same manner as in Example 1 except that the heating temperature was changed to 550 to 700°C.

[0070] Example 5

[0071] A medical wire was obtained in the same manner as in Example 1 except that the conditions of the plastic working at room temperature (25° C.) were changed.

[0072] Comparative Example 1

[0073] A medical wire was obtained in the same manner as in Example 1 except that the stretching annealing was not performed.

[0074] Comparative Example 2

[0075] A medical wire was obtained in the same manner as in Example 1 except that the drawn wire material 2 was used.

[0076] The hardness and tensile strength of the wire materials obtained in Examples 1 to 5 and Comparative Examples 1 and 2 were measured, and the recovery property was evaluated.

[0077] <Hardness measurement>

[0078] The wires of Examples 1 to 5 and Comparative Examples 1 to 2 were embedded in a resin and polished in such a manner that the cross section of the wire was perpendicular to the measuring axis (indenter axis). The cross section after polishing was subjected to nanoindentation hardness measurement based on the nanoindentation method (ISO 14577 "Instrumented Indentation Test") using a nanoindenter (iMicro) manufactured by KLA, using a diamond Berkovich indenter, under the conditions of a maximum indentation load of 30 mN and a dot interval of 0.01 mm.

[0079] Figure 2 This is a schematic diagram showing the results of measuring the cross section of a wire material using the nanoindentation method. Figure 2 The cross section of (a) is the measurement result of the wire rod of Example 1, Figure 2 The cross section (b) is the measurement result of the wire rod of Comparative Example 2. Each point of each cross section is a square of 0.01 mm square, corresponding to the measurement site. In addition, each point is color-coded so that the harder the hardness measured, the lighter the color, and it can be seen that the wire rod of Example 1 is harder as a whole.

[0080] In order to eliminate the influence of the resin used for embedding, the measurement points having a hardness of less than 7.0 GPa were excluded.

[0081] <Tensile test>

[0082] The tensile strength of the wire rods of Examples 1 to 5 and Comparative Examples 1 and 2 was measured by a tensile test of a metal wire rod (tensile test in accordance with JIS Z 2241 "Methods of tensile testing of metallic materials").

[0083] <Resilience Evaluation>

[0084] The wires of Examples 1 to 5 and Comparative Examples 1 to 2 were inserted into Figure 3 The residual angle of each wire after the groove 3 of the clamp 2 is shown.

[0085] Figure 3 This is a schematic diagram of a jig 2 used for restorability evaluation.

[0086] The first fixture 2 is made of resin (e.g., a transparent acrylic plate), and is composed of a first plate 2A having a groove 3 and a second plate 2B for covering the groove 3. The groove 3 of the first plate 2A is formed by a convex portion provided on the first plate 2A. The groove 3 has a pair of straight portions 3a and a semicircular arc portion 3b. The width of the groove 3 is 1.0 mm, and the depth of the groove 3 is 1.0 mm. The length of the straight portion 3a is 10 mm, and the radius R of the semicircular arc portion 3b is 10.0 mm. The second plate 2B abuts against the convex portion of the first plate 2A to cover the groove 3. The second plate 2B is fixed to the first plate 2A by four bolts 4.

[0087] Figure 4This is an explanatory diagram of the restoration evaluation.

[0088] Before loosening bolt 4( Figure 3 ) state, such as Figure 4 As shown in (a), a wire X cut into a predetermined length (e.g., 100 mm) is inserted into the groove 3, and the bolt 4 is tightened. Figure 4 As shown in (b), one end of the wire X is pressed into the opening of the groove 3 of the first clamp 2. Figure 4 As shown in (c), the other end of the wire X is pressed into the opening of the groove 3 of the first clamp 2. Figure 4 As shown in (d), one end of the wire X is pressed in, the center of the wire X is moved to the center of the groove 3, the bolt 4 is loosened, and the wire X is taken out. As a result, a strain (about 1.7) is applied to the entire wire X. The strain amount (%) is calculated by (R / (LR))×100. Here, R is the wire diameter of the wire X, and L is the diameter of the semicircular arc portion 3b of the groove 3 for the wire X to be inserted.

[0089] like Figure 5 As shown, tangent lines are drawn from both ends of the wire X, and the angle at which the two tangent lines intersect (residual angle θ) is measured.

[0090] Table 3 shows the results of the hardness measurement, tensile test, and recovery evaluation (residual angle).

[0091] [Table 2]

[0092]

[0093] Ave (whole) is the average hardness of all points on the cross section. Ave (periphery) is the average hardness of all points on the cross section. Figure 6 ) is the average value of hardness. Figure 6 Only shows Figure 2 The figure shows the points of the outer periphery C3 among all the points of the cross section of the wire rod.

[0094] As in the wire rods of Examples 1 to 5, by subjecting the wire drawing material composed of stable austenitic stainless steel to linear processing based on plastic deformation and then performing a stretch annealing treatment, the average hardness of the outer peripheral portion of the cross section becomes higher, thereby being able to form a wire rod with a small residual angle. In addition, the average hardness of the entire cross section of the wire rod becomes higher, and the hardness difference between the average hardness of the entire cross section of the wire rod and the average hardness of the outer peripheral portion of the cross section of the wire rod becomes smaller.

[0095] On the other hand, since the wire rod of Comparative Example 1 was not subjected to the drawing annealing treatment, the average hardness of the entire cross section of the wire rod was low and the residual angle was large. The wire rod of Comparative Example 2 was subjected to plastic working and drawing annealing treatment on the drawing material composed of SUS304, so that the average hardness of the entire cross section of the wire rod was equivalent to that of Example 5, but the hardness of the outer peripheral portion was low, so the residual angle was large.

[0096] It should be noted that the present disclosure is not limited to the configurations of the above-described embodiments but is shown by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims.

[0097] For example, in the above-mentioned embodiment, the medical wire is the core shaft 10 of the guide wire 1, but it can also be a wire constituting the coil body 20 or a wire used for other medical instruments, such as a wire constituting a reinforcing body (e.g., a cylindrical mesh assembly, a coil body) for reinforcing a catheter. By using the medical wire of the above-mentioned embodiment to constitute the coil body 20 or the reinforcing body of the catheter, the resilience of the coil body 20 or the reinforcing body after bending can be improved. In addition, for a coil made of the wire and a medical component composed of a hollow body, when a rotation operation is performed in a complex blood vessel, the excellent rotation tracking performance can be exerted in the same manner as described above.

[0098] Description of Reference Numerals

[0099] 1: guide wire, 10: core shaft, 20: coil body.

Claims

1. A medical wire made of stainless steel. The cross-section of the wire is a circle with a diameter of dmm. When the hardness of the cross section of the wire material was measured by nanoindentation, the average hardness of the outer peripheral portion consisting of the outer peripheral edge and a region surrounded by a circle having a distance d / 17 mm from the outer peripheral edge was 8.0 GPa or more.

2. The medical wire according to claim 1, wherein The stainless steel is a stable austenitic stainless steel, and the temperature Md of the stable austenitic stainless steel generating 50% of the work-induced martensite when a 30% strain is applied is given by Angel's formula. 30 Below -50℃.

3. The medical wire according to claim 2, wherein: The stable austenitic stainless steel is stainless steel according to ASTM F2581.

4. The medical wire according to any one of claims 1 to 3, wherein When the hardness of the cross section of the wire is measured by a nanoindentation method, the difference between an average value of the hardness of the entire cross section of the wire and an average value of the hardness of the peripheral portion is 0.7 GPa or less.

5. The medical wire according to any one of claims 1 to 4, wherein The average hardness of the entire cross section of the wire material is 8.9 GPa or more. 6 . A guide wire comprising the medical wire according to claim 1 .

Citation Information

Patent Citations

  • Guide wire core, manufacturing method of this core, and medical guide wire using this core

    JP2009172229A